Development of the Dukcapil Application In Setia Mekar Village - Mubarok, Ahmad Syahrul; Farhan, Dhia; Satria, Rian; Pamungkas, R Wisnu Prio (Yayasan Kita Menulis, 2024)
Technology will develop more and more every year. Many things currently use technology from various aspects, including general elections for government institutions in Indonesia. Data collection on general election participants in Indonesia is still relatively slow because data collection is still used manually and handwritten. The creation of this data collection system involved village government agencies including population administration and civil registration services (Dukcapil). This article discusses the design of the Dukcapil election application in Setiamekar Village which aims to simplify the administrative process and increase the efficiency of public services. The methods used in this design include needs analysis, system design, implementation and evaluation. The research results show that this application can help speed up the administration process, reduce manual errors, and increase public satisfaction.